(untitled) (Journal of Telenursing (JOTING), 2023)
This study aimed to determine the level of knowledge of hypertensive patients about medication adherence. The research method used is descriptive qualitative with a cross-sectional approach. The results showed that most of the 37 research samples were aged 51-65 years (59.4%), women (54.1%), a high education level (14%), self-employed (35.1%) stage two hypertension at the time of visit (86 .48%), many sufferers have a lack of knowledge (56.8%), and patients are not compliant in treatment (74.1%). In conclusion, most hypertension sufferers who seek treatment at the Internal Medicine Outpatient Unit at the Guido Valadares Nacional Hospital Dili Timor Leste have a poor level of knowledge, and most are also disobedient to their hypertension treatment. Keywords: Hypertension, Compliance, Level of Knowledge